2016
DOI: 10.1016/j.anorl.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Substernal goiter: Experience with 50 cases

Abstract: Substernal goitre is fairly frequent. Despite particularities, an exclusively cervical approach is sufficient in a large majority of cases. The substernal nature of the goitre did not have major impact on postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
1
12
0
6
Order By: Relevance
“…To assess the spread of mediastinal goiter, Benbakh et al classified 90% of patients according to the aortic arch and trachea in CT and they did not separate the thyroid lobes, as right and left, differently from ours. In this study, prevascular and aortic upper arch were the most common type of dissemination 16. According to the anatomical classification of Huins et al which is made before surgical approach by Dempsey et al, prior to the surgical approach, the spread of RSG above the aortic arch was the most common group 17.…”
Section: Discussionmentioning
confidence: 58%
“…To assess the spread of mediastinal goiter, Benbakh et al classified 90% of patients according to the aortic arch and trachea in CT and they did not separate the thyroid lobes, as right and left, differently from ours. In this study, prevascular and aortic upper arch were the most common type of dissemination 16. According to the anatomical classification of Huins et al which is made before surgical approach by Dempsey et al, prior to the surgical approach, the spread of RSG above the aortic arch was the most common group 17.…”
Section: Discussionmentioning
confidence: 58%
“…The most common complication is transient hypocalcemia, and its frequency is reported to range from 2 to 28.9%. On the other hand, it was reported that the frequency of permanent hypocalcemia ranges from 0 to 8.1% [ 1 , 2 , 5 , 6 , 16 ]. In the present case, transient hypocalcemia was observed, but it subsequently resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Historical factors worrisome for progressive obstruction include longstanding goiter, cough, dysphagia, hoarse voice, or superior vena cava syndrome (SVCS). 11 13 Exertional dyspnea is frequently experienced when tracheal diameter is compressed to less than eight millimeters, and stridor manifests when the lumen is less than five millimeters. 14 Positional changes, such as reaching forward, bending at the waist and lying supine, can provoke symptoms of obstruction.…”
Section: Resident Discussionmentioning
confidence: 99%